Nanopore-based targeted next-generation sequencing of tissue samples for tuberculosis diagnosis - Gao, Weiwei; Yang, Chen; Wang, Tianzhen; Guo, Yicheng; Zeng, Yi (Frontiers in Microbiology, 2024)
Diagnosing tuberculosis (TB) can be particularly challenging in the absence of sputum for pulmonary tuberculosis cases and extrapulmonary TB (EPTB). This study evaluated the utility of nanopore-based targeted next-generation sequencing (tNGS) for diagnosing TB in tissue samples, and compared its efficacy with other established diagnostic methods.A total of 110 tissue samples from clinical cases were examined. The sensitivity and specificity of tNGS were benchmarked against a range of existing diagnostic approaches including hematoxylin and eosin (HE) staining in conjunction with acid-fast bacilli (AFB) detection, HE staining combined with PCR, HE staining paired with immunohistochemistry (IHC) using anti-MPT64, and the Xpert Mycobacterium tuberculosis (MTB)/rifampicin (RIF) assay.The sensitivity and specificity of tNGS were 88.2% and 94.1%, respectively. The respective sensitivities for HE staining combined with AFB, HE staining combined with PCR, HE staining combined with IHC using anti-MPT64, and Xpert MTB/RIF were 30.1%, 49.5%, 47.3%, and 59.1%. The specificities for these methods were 82.4%, 88.2%, 94.1%, and 94.1%, respectively. Analysis of drug resistance based on tNGS results indicated that 10 of 93 TB patients (10.75%) had potential drug resistance.CONCLUSION: tNGS achieved higher accuracy than other established diagnostic methods, and can play a crucial role in the rapid and accurate diagnosis of TB, including drug-resistant TB.